Development of Ways to Improve the Energy Efficiency of Residential Buildings with Reinforced Concrete Tank Walls (Journal of Pedagogical Inventions and Practices, 2022)
The book is devoted to an important and relevant direction in the development of modern construction - energy-efficient reinforced concrete structures of buildings.